Effects of carbon nanotubes and carbon fibers on the properties of ultra-high performance concrete for offshore wind power generation - Chen, Jing (Center of Biomass & Renewable Energy (CBIORE), 2024)
Ultra-high performance concrete (UHPC), as one of the most eye-catching building materials, has been the subject of extensive research by scholars. On this basis, to expand the application of UHPC for offshore wind turbine towers in complex marine environments, three different fiber materials - copper-plated microfibre steel fibers, carbon fibers, and carbon nanotubes (CNTs) - have been selected for the study of the possibilities of further improving the mechanical properties of UHPC. This study focused on understanding the impact of various fiber combinations and dosages on the flowability, compressive strength, flexural strength, and tensile strength of UHPC. Our findings indicate that carbon fiber, when present at a concentration of up to 0.5%, the effect on the fluidity of UHPC is only about 1.05%. However, the addition of CNTs significantly diminishes the flowability of UHPC, with a consistent decrease observed as the CNT content increases. Notably, when carbon fiber and CNTs are used in combination, the maximum reduction in flowability reaches 7.8%. Furthermore, as the dosage of these fibers increases, the compressive strength, flexural strength, and tensile strength of UHPC all demonstrate a positive trend of improvement. It is observed that the optimal performance is achieved when both carbon fiber and CNTs are present. In particular, carbon fiber exhibits a more profound impact on enhancing compressive strength and flexural strength, when carbon fibers were doped by volume at 0.5%, the compressive and flexural strengths were increased by 6.7% and 11.7%, respectively, compared to the control group, while carbon nanotubes increased the tensile strength by 7.4% at lower dosage. These findings highlight the potential of fiber combinations to optimize UHPC’s mechanical properties for various engineering applications..